If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8u + -10 = 7u Reorder the terms: -10 + 8u = 7u Solving -10 + 8u = 7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7u' to each side of the equation. -10 + 8u + -7u = 7u + -7u Combine like terms: 8u + -7u = 1u -10 + 1u = 7u + -7u Combine like terms: 7u + -7u = 0 -10 + 1u = 0 Add '10' to each side of the equation. -10 + 10 + 1u = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 1u = 0 + 10 1u = 0 + 10 Combine like terms: 0 + 10 = 10 1u = 10 Divide each side by '1'. u = 10 Simplifying u = 10
| -9ab+8cd+3ab-8cd= | | -6(x+3)=-48 | | -8a-24= | | 4p-2=5p | | 5x+5y=220 | | 15x+20=2(2x-1) | | 9f+5=-3+10f | | 4[3(x+1)]+1=2(-31-x)+2x+31 | | -x^2+13x-22=0 | | -xy^2-3xy^2= | | 1+z=4+z | | 6a^2b+7a^2b= | | 3358/36 | | 2timesx+1=9 | | 2x-3(3x+3)=20 | | 3+27x=9.5+3.2x | | 3(x+y)+9(x+y)= | | 3x-4(2x-14)=31 | | 4x+5z=4 | | 0.4x-0.8x= | | 39x=3x-12 | | 2(x+5)=5(x+2) | | 1/7x=29/7 | | 5-6/7 | | f+3=y | | y*25/56=5/14 | | f=3y | | -10r^3+10r^3= | | 125+-4x=89 | | w*6/5=246 | | y+3=f | | x-4=2(3-2x) |